A method for preparing a high-toughness aluminum matrix composite

CN118147474BActive Publication Date: 2026-10-27JIANGSU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410302300.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-15
Publication Date
2026-10-27
Estimated Expiration
2044-03-15

AI Technical Summary

Technical Problem

陶瓷颗粒强化的铝基复合材料具有较高的强度,但陶瓷颗粒与铝基体间的结合性能较差导致铝基复合材料的塑性较差

Benefits of technology

[0023]本发明制备得到的铝基复合材料中的增强相分布均匀,制备的铝基复合材料在室温条件下的抗拉强度为380~420MPa,延伸率为14.8%~17.6%,能够较好地应用于实际工况条件下。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

The application provides a method for preparing high-strength and high-toughness aluminum matrix composite materials. In the application, a ceramic particle reinforced high-entropy alloy composite material is prepared by using a synchronous laser cladding technology, and then aluminum alloy powder, high-entropy alloy powder and the ceramic particle reinforced high-entropy alloy composite material are mixed to prepare the high-strength and high-toughness aluminum matrix composite material by using hot-pressing sintering and pre-deformation treatment. The ceramic particle reinforced high-entropy alloy composite material has the characteristics of metal materials, and the ceramic particle reinforced high-entropy alloy as the reinforcing phase has the advantages of ceramic particle reinforcing phase and metal particle reinforcing phase. Under the hot-pressing sintering and pre-deformation treatment, the ceramic particle reinforced high-entropy alloy can be combined well with the high-entropy alloy of the same composition, and then the intermetallic natural combination can form a very good metallurgical combination with the aluminum matrix. Therefore, the aluminum matrix composite material prepared by the application can have good strength and toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal material processing technology and relates to a method for preparing aluminum-based composite materials. Background Technology

[0002] Aluminum-based composites possess advantages such as light weight, high specific strength, high specific stiffness, and high elastic modulus, making them widely used lightweight materials in aerospace and rail transportation. However, with the rapid development of related fields, increasingly higher requirements are being placed on the comprehensive performance of aluminum-based composites. Ceramic particle-reinforced aluminum-based composites exhibit high strength, but the poor bonding between ceramic particles and the aluminum matrix leads to poor plasticity. Metal particle-reinforced aluminum-based composites have better bonding with the aluminum matrix and good plasticity, but their strength is relatively poor. It is evident that it is difficult to simultaneously improve the strength and toughness of aluminum-based composites, limiting their widespread application in industrial production. Therefore, exploring a method for preparing ultra-high strength and toughness aluminum-based composites has significant research and application value. Summary of the Invention

[0003] To address the shortcomings of existing technologies, this invention provides a method for preparing high-strength and high-toughness aluminum-based composite materials. In this invention, a ceramic particle-reinforced high-entropy alloy composite material is first prepared using synchronous laser cladding technology. Then, aluminum alloy powder, high-entropy alloy powder, and the ceramic particle-reinforced high-entropy alloy composite material are mixed, and the high-strength and high-toughness aluminum-based composite material is prepared using hot-pressing sintering and pre-deformation treatment. Since high-entropy alloys are solid solutions composed of multi-component elements with near-equiatomic ratios, they exhibit good bonding with the aluminum matrix and ceramic particles. The ceramic particle-reinforced high-entropy alloy composite material possesses metallic properties. Using the ceramic particle-reinforced high-entropy alloy as a reinforcing phase combines the advantages of both ceramic and metallic reinforcing phases. Under hot-pressing sintering and pre-deformation treatment, the ceramic particle-reinforced high-entropy alloy first bonds well with other high-entropy alloys of the same composition, and then, through natural intermetallic bonding, forms a very good metallurgical bond with the aluminum matrix. Therefore, the aluminum-based composite material prepared by this invention possesses both good strength and toughness.

[0004] This invention first provides a method for preparing a high-strength and high-toughness aluminum-based composite material, wherein no reinforcing phase aggregation occurs in the aluminum-based composite material, and the tensile strength of the aluminum-based composite material at room temperature is 380-420 MPa and the elongation is 14.8%-17.6%.

[0005] Furthermore, the aluminum alloy is one of the 5-series, 6-series, or 7-series aluminum alloys.

[0006] Furthermore, the ceramic particles are TiC particles, and the high-entropy alloy is a FeCoNiCrMn-based high-entropy alloy.

[0007] This invention provides a method for preparing an aluminum-based composite material, specifically comprising the following steps:

[0008] (1) Vacuum atomized high-entropy alloy powder and ceramic particle powder are ball-milled and mixed. The mass ratio of ceramic particles to high-entropy alloy powder is 10-20:100 to obtain uniform composite powder.

[0009] (2) Using ultrasonic-assisted laser cladding technology, composite materials are prepared using the composite powder obtained in step (1). The ultrasonic-assisted process parameters are as follows: ultrasonic vibration frequency is 10-40KHz, and ultrasonic vibration power is 1000-5000W.

[0010] (3) The composite material obtained in step (2) is cut into 3mm×3mm×3mm particles using slow wire EDM technology. The slow wire EDM speed is 1mm / s.

[0011] (4) Vacuum atomized aluminum alloy powder and high entropy alloy powder are ball-milled and mixed. The mass ratio of aluminum alloy powder to high entropy alloy powder is 100:10~20 to obtain uniform composite powder.

[0012] (5) The composite powder obtained in step (4) and the particles obtained in step (3) are ball-milled and mixed, with the mass ratio of composite powder to particles being 100:10-20.

[0013] (6) Place the composite powder obtained in step (5) into a hot press mold, then heat and keep it warm, use a press to perform hot pressing sintering treatment, and finally use an ejector to eject the prepared hot press blank. The holding temperature is 450-500℃ and the holding time is 60-80min.

[0014] (7) The hot-pressed billet obtained in step (6) is subjected to free forging pre-deformation treatment and heat treatment, and then the oxide layer is removed to obtain the finished product. The pre-deformation reduction is 3-8%.

[0015] Furthermore, in step (1), the high-entropy alloy powder has a size of 15-105 μm, and the ceramic particles have a size of 0.5-2 μm.

[0016] Further, in step (2), the process parameters of the laser cladding are as follows: laser power is 1200-2000W, spot diameter is 2-6mm, scanning speed is 5-10mm / s, overlap rate is 40-60%, and powder feeding speed is 6-14g / min.

[0017] Furthermore, in step (3), the diameter of the copper wire used in the slow wire EDM is 0.25 mm.

[0018] Furthermore, in step (4), the aluminum alloy powder particle size is 15-105μm, and the composition and particle size of the high entropy alloy powder are the same as those in step (1).

[0019] Furthermore, in step (5), the ball milling speed is 400-600 rpm and the ball milling time is 12 h.

[0020] Furthermore, in step (6), the pressure for holding the pressure is 200-600 MPa.

[0021] Furthermore, in step (7), the heat treatment temperature is 450-550℃ and the time is 2-4h.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0023] The reinforcing phase in the aluminum-based composite material prepared by this invention is uniformly distributed. The tensile strength of the prepared aluminum-based composite material at room temperature is 380-420 MPa, and the elongation is 14.8%-17.6%, which can be well applied to actual working conditions.

[0024] Ceramic particle-reinforced aluminum matrix composites exhibit high strength, but the poor bonding between the ceramic particles and the aluminum matrix results in poor plasticity. Metal particles, on the other hand, have better bonding with the aluminum matrix, leading to good plasticity in metal particle-reinforced aluminum matrix composites, but their strength is relatively poor. This invention provides a method for preparing high-strength and high-toughness aluminum matrix composites. In this invention, a ceramic particle-reinforced high-entropy alloy composite material is first prepared using synchronous laser cladding technology. Then, aluminum alloy powder, high-entropy alloy powder, and the ceramic particle-reinforced high-entropy alloy composite material are mixed, and the high-strength and high-toughness aluminum matrix composite material is prepared using hot pressing sintering and pre-deformation treatment. Since high-entropy alloys are solid solutions composed of multiple elements in near-equal atomic ratios, they exhibit good bonding with the aluminum matrix and ceramic particles. High-entropy alloy composites reinforced with ceramic particles possess metallic properties. Using high-entropy alloys reinforced with ceramic particles as a reinforcing phase combines the advantages of both ceramic and metallic reinforcing phases. Under hot pressing sintering and pre-deformation treatment, the ceramic-reinforced high-entropy alloys can first bond well with high-entropy alloys of the same composition, and then form a very good metallurgical bond with the aluminum matrix through natural bonding between metals. Therefore, the aluminum-based composite material prepared by this invention can possess both good strength and toughness. Attached Figure Description

[0025] Figure 1 This is a microstructure diagram of the aluminum-based composite material prepared in Example 1 of the present invention. Detailed Implementation

[0026] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0027] Example 1:

[0028] (1) Vacuum atomized high-entropy alloy powder and ceramic particles are ball-milled and mixed. The mass ratio of ceramic particles to high-entropy alloy powder is 15:100. The size of high-entropy alloy powder is 15-105μm and the size of ceramic particles is 0.5-2μm to obtain uniform composite powder.

[0029] (2) Using ultrasonic-assisted laser cladding technology, composite materials are prepared using the composite powder obtained in step (1). The ultrasonic vibration frequency is 20KHz, the ultrasonic vibration power is 2000W, the laser power is 1600W, the spot diameter is 4mm, the scanning speed is 8mm / s, the overlap rate is 50%, and the powder feeding speed is 10g / min.

[0030] (3) The composite material obtained in step (2) is cut into 3mm×3mm×3mm particles using slow wire EDM technology. The slow wire EDM speed is 1mm / s and the diameter of the copper wire used for slow wire EDM is 0.25mm.

[0031] (4) The vacuum-atomized aluminum alloy powder and the high-entropy alloy powder are ball-milled and mixed. The mass ratio of aluminum alloy powder to high-entropy alloy powder is 100:15. The particle size of aluminum alloy powder is 15-105μm. The composition and particle size of high-entropy alloy powder are the same as those of high-entropy alloy powder in step (1) to obtain a uniform composite powder.

[0032] (5) The composite powder obtained in step (4) and the particles obtained in step (3) are ball-milled and mixed. The mass ratio of composite powder to particles is 100:15, the ball milling speed is 500 rpm, and the ball milling time is 12 h.

[0033] (6) Place the composite powder obtained in step (5) into a hot press mold, then heat and keep it warm, use a press to perform hot pressing sintering treatment, and finally use an ejector to eject the prepared hot press blank. The holding temperature is 480℃, the holding time is 70min, and the holding pressure is 400MPa.

[0034] (7) The hot-pressed billet obtained in step (6) is subjected to free forging pre-deformation treatment and heat treatment, and then the oxide layer is removed to obtain the finished product. The pre-deformation reduction is 5%, the heat treatment temperature is 500℃, and the time is 3h.

[0035] The microstructure of the prepared aluminum-based composite material was characterized, and its room-temperature tensile mechanical properties were tested to meet national standards. For example... Figure 1The reinforcing phase particles in the aluminum matrix composite are uniformly distributed, with a tensile strength of 420 MPa and an elongation of 17.6%.

[0036] Example 2:

[0037] It is basically the same as Example 1, but with the following changes: the laser power in step (2) is 1200W.

[0038] The prepared aluminum-based composite material was subjected to room temperature tensile mechanical property tests that meet national standards. The tensile strength was 380 MPa and the elongation was 14.8%.

[0039] Example 3:

[0040] It is basically the same as Example 1, but with the following changes: the laser power in step (2) is 2000W.

[0041] The prepared aluminum-based composite material was subjected to room temperature tensile mechanical property tests that meet national standards. The tensile strength was 400 MPa and the elongation was 15.6%.

[0042] Example 4:

[0043] It is basically the same as Example 1, but with the following changes: the holding pressure in step (6) is 200 MPa.

[0044] The prepared aluminum-based composite material was subjected to room temperature tensile mechanical property tests that meet national standards. The tensile strength was 392 MPa and the elongation was 15.1%.

[0045] Example 5:

[0046] It is basically the same as Example 1, but with the following changes: the holding pressure in step (6) is 600 MPa.

[0047] The prepared aluminum-based composite material was subjected to room temperature tensile mechanical property tests that meet national standards. The tensile strength was 405 MPa and the elongation was 15.8%.

[0048] Comparative Example 1:

[0049] (1) Vacuum atomized aluminum alloy powder and high entropy alloy powder are ball-milled and mixed. The mass ratio of aluminum alloy powder to high entropy alloy powder is 100:15. The size of aluminum alloy powder is 15-105μm and the size of high entropy alloy powder is 15-105μm, so as to obtain uniform composite powder.

[0050] (2) Place the composite powder obtained in step (1) into a hot press mold, then heat and keep it warm, and use a press to perform hot pressing sintering treatment. The holding temperature is 480℃, the holding time is 70min, the holding pressure is 400MPa, and finally use an ejector device to eject the prepared hot press blank.

[0051] (3) The hot-pressed billet obtained in step (2) is subjected to free forging pre-deformation treatment and heat treatment, and then the oxide layer is removed to obtain the finished product. The pre-deformation reduction is 5%, the heat treatment temperature is 500℃, and the time is 3h.

[0052] The prepared aluminum-based composite material was subjected to room temperature tensile mechanical property tests that meet national standards. The tensile strength was 285 MPa and the elongation was 13.9%.

[0053] Comparative Example 2:

[0054] (1) Vacuum atomized aluminum alloy powder and ceramic particles are ball-milled and mixed. The mass ratio of aluminum alloy powder to ceramic particles is 100:15. The size of aluminum alloy powder is 15-105μm and the size of ceramic particles is 0.5-2μm, so as to obtain a uniform composite powder.

[0055] (2) Place the composite powder obtained in step (1) into a hot press mold, then heat and keep it warm, and use a press to perform hot pressing sintering treatment. The holding temperature is 480℃, the holding time is 70min, the holding pressure is 400MPa, and finally use an ejector to eject the prepared hot press blank.

[0056] (3) The hot-pressed billet obtained in step (2) is subjected to free forging pre-deformation treatment and heat treatment, and then the oxide layer is removed to obtain the finished product. The pre-deformation reduction is 5%, the heat treatment temperature is 500℃, and the time is 3h.

[0057] The prepared aluminum-based composite material was subjected to room temperature tensile mechanical property tests that meet national standards. The tensile strength was 372 MPa and the elongation was 8.8%.

[0058] The embodiments described above are preferred embodiments of the present invention, but the present invention is not limited to the above embodiments. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essence of the present invention shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-strength and high-toughness aluminum-based composite material, characterized in that, Specifically, the steps include the following: (1) Vacuum atomized high-entropy alloy powder and ceramic particles are ball-milled and mixed, with the mass ratio of ceramic particles to high-entropy alloy powder being 10-20:100, to obtain uniform composite powder. (2) Using ultrasonic-assisted laser cladding technology, composite materials are prepared using the composite powder obtained in step (1). The ultrasonic-assisted process parameters are as follows: ultrasonic vibration frequency is 10-40KHz, and ultrasonic vibration power is 1000-5000W. (3) The composite material obtained in step (2) is cut into 3mm×3mm×3mm particles using slow wire EDM technology. The slow wire EDM speed is 1mm / s. (4) Vacuum atomized aluminum alloy powder and high entropy alloy powder are ball-milled and mixed. The mass ratio of aluminum alloy powder to high entropy alloy powder is 100:10~20 to obtain uniform composite powder. (5) The composite powder obtained in step (4) and the particles obtained in step (3) are ball-milled and mixed, with the mass ratio of composite powder to particles being 100:10~20. (6) Place the composite powder obtained in step (5) into a hot press mold, then heat and keep it warm, use a press to perform hot pressing sintering treatment, and finally use an ejector to eject the prepared hot press blank. The holding temperature is 450~500℃ and the holding time is 60~80min. (7) The hot-pressed billet obtained in step (6) is subjected to free forging pre-deformation treatment and heat treatment, and then the oxide layer is removed to obtain the finished product. The pre-deformation reduction is 3~8%; The high-entropy alloy powders in steps (1) and (4) are of the same composition and have the same particle size.

2. The method for preparing the high-strength and high-toughness aluminum-based composite material according to claim 1, characterized in that, In step (1), the high-entropy alloy powder has a size of 15-105 μm and the ceramic particles have a size of 0.5-2 μm.

3. The method for preparing the high-strength and high-toughness aluminum-based composite material according to claim 1, characterized in that, In step (2), the laser cladding process parameters are as follows: laser power is 1200-2000W, spot diameter is 2-6mm, scanning speed is 5-10mm / s, overlap rate is 40-60%, and powder feeding speed is 6-14g / min.

4. The method for preparing the high-strength and high-toughness aluminum-based composite material according to claim 1, characterized in that, In step (3), the diameter of the copper wire used in the slow wire EDM is 0.25 mm.

5. The method for preparing the high-strength and high-toughness aluminum-based composite material according to claim 1, characterized in that, In step (4), the aluminum alloy powder size is 15-105μm, and the composition and particle size of the high entropy alloy powder are the same as those in step (1).

6. The method for preparing the high-strength and high-toughness aluminum-based composite material according to claim 1, characterized in that, In step (5), the ball milling speed is 400~600 rpm and the ball milling time is 12h.

7. The method for preparing the high-strength and high-toughness aluminum-based composite material according to claim 1, characterized in that, In step (6), the pressure for holding pressure is 200~600MPa.

8. The method for preparing the high-strength and high-toughness aluminum-based composite material according to claim 1, characterized in that, In step (7), the heat treatment temperature is 450-550℃ and the time is 2-4h.

9. A high-strength and high-toughness aluminum-based composite material prepared according to any one of claims 1 to 8, characterized in that, The ultra-high strength aluminum matrix composite material has a tensile strength of 380~420MPa and an elongation of 14.8%~17.6% at room temperature.

10. The high-strength and high-toughness aluminum-based composite material according to claim 9, characterized in that, The aluminum alloy is one of the 5-series, 6-series, or 7-series aluminum alloys.

11. The high-strength and high-toughness aluminum-based composite material according to claim 9, characterized in that, The ceramic particles are TiC particles, and the high-entropy alloy is a FeCoNiCrMn-based high-entropy alloy.

Citation Information

Patent Citations

  • High-entropy alloy particle reinforced aluminum matrix composite material and magnetic field assisted preparation method

    CN112899531A

  • A multi-component shape memory high-entropy alloy for additive manufacturing and its preparation method

    CN116809940A

  • NANO ceramic metal composite powder for 3D printing, and application

    WO2022041258A1